Frequency and Socio-demographic Characteristics of Patients presented with Ovarian Tumour at a tertiary care hospital - Zakaria, Rooh E; Dewan, Farhana; Yusuf, Md Abdullah; Rahman, Mamunur; Hauque, Mojammel (Journal of Shaheed Suhrawardy Medical College, 2017)
Background: Ovarian tumour causes great morbidity and mortality. Objective: The purpose of the present study was to analyze the different presentation of ovarian tumours to see the frequency and clinic-demographic characteristics of ovarian tumour. Methodology: This cross sectional study was conducted in the Department of Gynaecology & Obstetrics, Shaheed Suhrawardy Medical College, Dhaka during the period from January to June 2013 for a period of six months. Patient admitted in Department of Obstetrics Gynaecology ward in Shaheed Suhrawardy Medical College Hospital with provisional diagnosis of ovarian tumour were selected as study population. Proper permission was taken from the ethical committee of Shaheed Suhrawardy Medical College Hospital for this study. All the patients were informed about the various aspects of the study. Their verbal consents were taken. Women of all ages with ovarian tumour were included in this study. Women with all other tumour except ovarian tumour were excluded from this study. A thorough history variably collected, clinical examination and investigations was carried out. The result of benign and malignant ovarian neoplasms in regard to age parity, physical sign, vaginal examination, laparotomy findings, together with their macroscopic findings are tabulated separately. Histopathological examination was done by senior pathologists of ShSMCH. Result: A total 50 cases of ovarian tumour had been studied of which 26 (52%) were benign and 24(49%) were malignant ovarian tumours which were confirmed by histopathological examination (P>0.05). 28% and 12% patient with benign ovarian tumour were in age group of 18-34 years and 35-45 years and 14% patient with malignant ovarian tumour in age group >45 years (p>0.05). 32% patient with benign ovarian tumours came from poor socio economics condition and 20% from middle class, 28% patient with malignant ovarian tumour came from poor and 16% from middle class family. Out of 50 cases of ovarian tumour , 39 were married and 11 were unmarried. 51% patients did not use any contraceptives and 31% oral contraceptives (P<0.05). No family history was found in 92% patients. 16% patients with benign tumours were unmarried. Conclusion: In conclusion ovarian tumour are mostly benign of which middle age group are most commonly reported. J Shaheed Suhrawardy Med Coll, 2014; 6(2):76-78